Performance of biocement treatment in improving the interfacial properties of recycled aggregate concrete. (10th March 2023) - Mistri, Abhijit; Dhami, Navdeep; Bhattacharyya, Sriman Kumar; Barai, Sudhirkumar V.; Mukherjee, Abhijit
Highlights: Strengthening of RCA via cement slurry and biocement treatment was performed. Both the control and treated aggregates are characterised for its possible use. A novel method of fabricating concrete cubes with one aggregate has been developed. Micromechanical property using nanoindentation was assessed at concrete interface. RCA can be used to replace the NCA without compromising its performance. Abstract: Variable quality of recycled aggregates especially attached mortars leading to weak interfaces is a primary drawback of recycled coarse aggregate (RCA). This investigation explores strengthening of such aggregates by biocement treatment and compares it with the conventional cement slurry treatment. The effect of the treatments on the aggregates has been recorded in terms of water absorption and mechanical properties. To study the concrete-aggregate interface, a novel method of fabricating concrete cubes with one aggregate has been developed. Damage evolution at the interfaces has been recorded with advanced monitoring techniques. Microstructural behaviour and elemental composition in the interface were also recorded. The test results show that the biocement treatment reduces the water absorption of RCA by about 71%. A microstructural study demonstrates that biocement, due to its considerably low viscosity, is able to penetrate the porous interfacial mortar within RCA and densify it. The micromechanical properties using nanoindentation provides more insights in improving of interfacial transition zones. The treatment improves the aggregates to a level that it can be used to replace the natural aggregates without compromising its performance.